Li+‐Containing, Continuous Silica Nanofibers for High Li+ Conductivity in Composite Polymer Electrolyte. Issue 44 (9th September 2019) - Yu, Jianming; Wang, Chao; Li, Shiheng; Liu, Nian; Zhu, Jia; Lu, Zhenda
Abstract: Solid‐state electrolytes have recently attracted significant attention toward safe and high‐energy lithium chemistries. In particular, polyethylene oxide (PEO)‐based composite polymer electrolytes (CPEs) have shown outstanding mechanical flexibility and manufacturing feasibility. However, their limited ionic conductivity, poor electrochemical stability, and insufficient mechanical strength are yet to be addressed. In this work, a novel CPE supported by Li + ‐containing SiO2 nanofibers is developed. The nanofibers are obtained via sol–gel electrospinning, during which lithium sulfate is in situ introduced into the nanofibers. The uniform doping of Li2 SO4 in SiO2 nanofibers increases the Li + conductivity of SiO2, generates mesopores on the surface of SiO2 nanofibers, and improves the wettability between SiO2 and PEO. As a result, the obtained SiO2 /Li2 SO4 /PEO CPE yields high Li + conductivity (1.3 × 10 −4 S cm −1 at 60 °C, ≈4.9 times the Li2 SO4 ‐free CPE) and electrochemical stability. Furthermore, the all‐solid‐state LiFePO4 ‐Li full cell demonstrates stable cycling with high capacities (over 80 mAh g −1, 50 cycles at C/2 at 60 °C). The Li + ‐containing mesoporous SiO2 nanofibers show great potential as the filler for CPEs. Similar methods can be used to incorporate Li salts into other filler materials for CPEs. Abstract : A novel Li + ‐containing mesoporous SiO2 nanofibers network reinforced composite solid electrolyte is developed through Li‐slat‐modified electrospinning and polymer electrolyte wetting. The obtained SiO2 /Li2 SO4 / polyethylene oxide composite polymer electrolyte demonstrates a high Li + conductivity of ≈1.3 × 10 −4 S cm −1 at 60 °C and yields high cycling stability in Li symmetric cell and LiFePO4 ‐Li all‐solid‐state cell configurations.